Evaluación de la usabilidad de un Objeto de Aprendizaje por estudiantes - Pesado, Patricia Mabel (2012)
The discussion about the quality of Learning Object (LO) has had various approaches over time related to the conception and definition it has been assumed.\nConsidering a LO as a digital Web resource, could rescue assessment criteria as Web sites. As a pedagogical purpose, criteria should relate primarily the user, the content and specific goals.\nThis paper presents a proposal for evaluation from the perspective of end users: students. Although it could be a LO positively assessed by experts, is intended to define many issues about its valuation such as difficulty in understanding, if the LO has elements that facilitate learning among others. To do this, we built a satisfaction questionnaire that integrates pedagogical and technical dimensions. The results of its implementation were combined with analysis of self reporting logs captured in a virtual teaching and learning environment (VLE) after the interaction from each of students with LO.\nFinally we present the application of this methodology to a LO for initial programming course.